Increased Medial Prefrontal Cortex and Decreased Zygomaticus Activation in Response to Disliked Smiles Suggest Top-Down Inhibition of Facial Mimicry - Korb, Sebastian; Goldman, Robin; Davidson, Richard J.; Niedenthal, Paula M. (Frontiers in Psychology, 2019)
Spontaneous facial mimicry is modulated by many factors, and often needs to be suppressed to comply with social norms. The neural basis for the inhibition of facial mimicry was investigated in a combined functional magnetic resonance imaging (fMRI) and electromyography (EMG) study in 39 healthy participants. In an operant conditioning paradigm, face identities were associated with reward or punishment and were later shown expressing dynamic smiles and anger expressions. Face identities previously associated with punishment, compared to reward, were disliked by participants overall, and their smiles generated less mimicry. Consistent with previous research on the inhibition of finger/hand movements, the medial prefrontal cortex (mPFC) was activated when previous conditioning was incongruent with the valence of the expression. On such trials there was also greater functional connectivity of the mPFC with insula and premotor cortex as tested with psychophysiological interaction (PPI), suggesting inhibition of areas associated with the production of facial mimicry and the processing of facial feedback. The findings suggest that the mPFC supports the inhibition of facial mimicry, and support the claim of theories of embodied cognition that facial mimicry constitutes a spontaneous low-level motor imitation.